The Role of pHi in Intestinal Epithelial Proliferation–Transport Mechanisms, Regulatory Pathways, and Consequences - Amiri, Mahdi; Seidler, Ursula E.; Nikolovska, Katerina (Frontiers in Cell and Developmental Biology, 2021)
During the maturation of intestinal epithelial cells along the crypt/surface axis, a multitude of acid/base transporters are differentially expressed in their apical and basolateral membranes, enabling processes of electrolyte, macromolecule, nutrient, acid/base and fluid secretion and absorption. An intracellular pH (pHi)-gradient is generated along the epithelial crypt/surface axis, either as a consequence of the sum of the ion transport activity, or as a distinctly regulated entity. While the role of pHi on proliferation, migration and tumorigenesis has been explored in cancer cells for some time, emerging evidence suggests an important role of the pHi in the intestinal stem cells (ISCs) proliferative rate under physiological conditions. The present review highlights the current state of knowledge about the potential regulatory role of pHi on proliferation, with focus on the intestinal epithelium.